SOME OBSERVATIONS ON BEHAVIOUR OF SPOTTED OWLET (Athene brama) DURING ITS BREEDING SEASON - M. Mahmood-ul-Hassan (Journal of Animal and Plant Sciences, 2008)
Foraging, courtship and mating behavior in a pair of spotted owlet (Athene brama) in Punjab, Pakistan was monitored. A total of 360 hours was spent in observing this pair. Observations made from 1700 to 2000 hours Pakistan standard Time (PST) from 15 February to 15 May 2002 revealed that no clear cut sexual dimorphism exists in this species and sexes were judged from the relative position of birds during mating. The owlets are mainly crepuscular. Immediately after emerging from their nest, they stretch their wings and legs (2.52 min ± 65 sec; n = 78), self-preen (2.12 min ± 45 sec; n = 93) and leave for foraging after emitting loud territorial calls. They use “sit and wait” strategy to capture their prey and perch on electric lamp posts 5 - 10 m high from the ground. Two instances of courting and mating were also observed.
Keywords: Behaviour; Courtship; Display; Mating; Mobbing